Hermeneutic Phenomenology Method for Investigating the Factors Contributing to Educational Students' Lack of Interest in Becoming Teachers - Widiyanto Widiyanto (Journal of Economic Education, 2023)
This study aims to investigate the factors that cause students in an educational study program not to want to become teachers. A qualitative hermeneutic phenomenology research method was used. The objective of this study is to identify the factors that make education students unwilling to work as teachers. The research locus is at UNNES, with several UNNES student informants from five faculties participating. According to the study's findings, the categories that influence career choice outside of education are intrinsic factors, extrinsic factors, and outcome prospects and opportunities. Interpersonal relationships, intrapersonal relationships, career prospects, and opportunities all have a significant impact on the decision to pursue a career other than teaching. Hobbies are another finding that can be considered a new variable that has never been studied.